Micro Impacts of Macroeconomic Adjustment Policies (MIMAP): The Philippine Case - Caesar B. Cororaton; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 1996)
While adjustment policies are necessary to realign the economy in the right track, it entails a number of adverse impacts, especially on the poor and vulnerable groups. This paper reviews the Philippine growth performance, its economic structure and the reforms it has implemented. This also discusses the major components of MIMAP project and the simulation results generated
Keywords: 330; macroeconometric model; tariff reduction; nominal tariff rate; average tariff rate